FAKTOR-FAKTOR YANG MEMENGARUHI PEMILIHAN PROGRAM STUDI DENGAN MINAT MAHASISWA SEBAGAI VARIABEL INTERVENING DI PERGURUAN TINGGI SWASTA DI JAKARTA - Caswito, Ade; Lisdiana, Lisdiana; Hidayat, Taufik; Abdullah, M. Thufail; Qalbi, Nabila Asyifa (Jurnal Maneksi (Management Ekonomi Dan Akuntansi), 2025)
Introduction: The mismatch between interests and study program selection remains a challenge at many Private Universities (PTS) in Jakarta. This inaccuracy negatively impacts student enthusiasm for learning, academic achievement, and dropout rates. This study aims to analyze factors influencing the decision to choose a study program (Y), with Student Interest (Z) as an intervening variable. The independent variables used include Facilities and Service Facilities (X1), Education Fees (X2), Marketing Communication (X3), Lecturer Competence (X4), Job Prospects (X5), Self-Motivation (X6), and Family Support (X7)Methods: This study used a quantitative method, distributing questionnaires to 119 students at several private universities in Jakarta, and analyzed the data using multiple regression, classical assumption tests, the Sobel test, and the coefficient of determination (Adjusted R²).Results: The research findings show that Job Prospects (X5), Self-Motivation (X6), and Family Support (X7) impact students’ bias in choosing a study program, while other variables do not have a significant effect. The Sobel test indicates that Student Interest (Z) mediates only the influence of Self-Motivation (X6). The research model is valid with R² = 0.733 and Adjusted R² = 0.713. These findings confirm the importance of motivation, family support, and job prospects in students’ academic decisions.Conclusion and suggestion: Job prospects, self-motivation, and family support significantly influenced the decision to choose a study program, while other factors did not. Student interests did not mediate the effect of self-motivation. Universities need to strengthen career guidance and emphasize job prospects to facilitate informed study decisions. Keywords: Five words, Alphabet